Polska, Unia Europejska i kryzys. Czy Polacy winią Europę? - Liszowska, Julia (Political Preferences, 2013)
The paper focuses both on results of own reseach (national poll conducted in Poland) and results of other polls concerning perception of the impact of the crisis in Poland. The results were analyzed in terms of correlation between political preferences (both partisan and ideological) and perceived severity of the crisis in Poland, as well as relationship between political preferences and seeing the EU as cause of the crisis in Poland, or at least reason behind growing seriousness of its signs in Poland. A vast array of other polls - both national and European (mainly euro- barometer, but not only), as well as global - were analyzed, to verify whethere opinions of the Poles changed over time, and how they place in comparison with views of other nations. Overall, the Poles seem less pessimistic regarding the crisis than other nations, mainly due to comparatively better economic outlook, and their opinion on Polish membership in the EU remains very strongly positive. A significant percentage of respondents blamed - at least in part - EU for the crisis, but it did not translate into negative view on EU accession overall.